2019
DOI: 10.1039/c9ta05247j
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial engineering of gallium indium phosphide photoelectrodes for hydrogen evolution with precious metal and non-precious metal based catalysts

Abstract: A nanoscale molybdenum disulfide (MoS2) film functions both as an effective protection layer and excellent hydrogen evolution catalyst for GaInP2 photocathodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 58 publications
3
27
0
Order By: Relevance
“…Molybdenum disulfide nanomaterials have been shown to stabilize a variety of singlejunction Si and III-V PEC systems, functioning as a hydrogen evolution reaction (HER) catalyst and protection layer. [9][10][11][12][13][14][15] Because of the promising performance in single-junction photocathodes, it is of interest to use MoS2 with tandem semiconductor systems to improve the stability during unassisted solar water splitting.…”
Section: Toc Graphicmentioning
confidence: 99%
See 2 more Smart Citations
“…Molybdenum disulfide nanomaterials have been shown to stabilize a variety of singlejunction Si and III-V PEC systems, functioning as a hydrogen evolution reaction (HER) catalyst and protection layer. [9][10][11][12][13][14][15] Because of the promising performance in single-junction photocathodes, it is of interest to use MoS2 with tandem semiconductor systems to improve the stability during unassisted solar water splitting.…”
Section: Toc Graphicmentioning
confidence: 99%
“…16 An MoS2 coating was deposited on the MoS2/pn-GaInAsP/pn-GaAs device (hereby known as MoS2/III-V) by sputtering a nominal 3.6 nm Mo metal film followed by a thermal partial sulfidization (Figure 1). [9][10][11] This MoS2 coating procedure is identical to that performed in a previous study on MoS2-coated GaInP2 phocathodes; X-ray photoelectron spectroscopy (XPS) demonstrated that the catalyst coating comprised a mixture of MoS2, metallic Mo, and MoOx. 9 In another work developing MoS2/n + p-Si photocathodes with a MoS2 deposition process utilizing a slightly higher sulfidization temperature but otherwise identical to that in this work, cross-sectional transmission electron microscopy (TEM) imaging demonstrated a thickness of ~5 nm, with MoS2 sheets residing on top of a thin metallic Mo layer.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, transition‐metal phosphides (TMPs) are considered to be one of the most studied electrocatalytic materials at present [23–25] . However, monometal TMPs usually have poor electroconductivities and inferior stabilities, thus significantly limiting their expected catalytic activities [26–28] . For this reason, multicomponent TMPs have been developed and have proven to be feasible alternatives for enhancing catalytic performance, both in theory and practice [3,29,30] .…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] However, monometal TMPs usually have poor electroconductivities and inferior stabilities, thus significantly limiting their expected catalytic activities. [26][27][28] For this reason, multicomponent TMPs have been developed and have proven to be feasible alternatives for enhancing catalytic performance, both in theory and practice. [3,29,30] In NiÀ FeÀ P, for example, density functional theory (DFT) calculations have revealed that the electronic structure of the NiÀ P catalyst can be readily tuned with the help of extra Fe 3d states at the Fermi level, greatly reducing the charge transfer resistance and thus promoting its OER activity.…”
Section: Introductionmentioning
confidence: 99%